THE RELATIONSHIP BETWEEN ORGANIZATIONAL COMMITMENT AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR IN PRIVATE MANUFACTURING COMPANIES - Mark, Alla (Universiti Malaysia Sarawak (UNIMAS), 2021)
This chapter consists of nine sections in total. The first section discusses about research background. The second section of this research states the problem statement in the research. The third section states the research objectives and the fourth section discusses the research hypothesis. The fifth section explains the conceptual framework of the research and the sixth section defines the terms used in this research. The significance of research discussed in the seventh section. Section eight discusses the limitation of the research. The ninth section is the conclusion for this chapter.